A review of screening strategies for cervical cancer in human immunodeficiency virus-positive women in sub-Saharan Africa - Viviano M; DeBeaudrap P; Tebeu PM; Fouogue JT; Vassilakos P; Petignat P (Dove Medical Press, 2017)
Manuela Viviano,1 Pierre DeBeaudrap,2 Pierre-Marie Tebeu,3 Jovanny T Fouogue,3 Pierre Vassilakos,4 Patrick Petignat1 1Gynecology Division, Geneva University Hospitals, Geneva, Switzerland; 2Centre Population et Développement – UMR 196, Institute of Research for the Development, University of Paris-Descartes, Paris, France; 3Faculty of Medicine and Biomedical Sciences and Centre Hospitalier Universitaire (CHUY), Yaoundé, Cameroon, Africa; 4Geneva Foundation for Medical Education and Research, Geneva, Switzerland Abstract: Cervical cancer (CC) is a leading cause of cancer-related death and a major public health issue in sub-Saharan Africa. This heavy burden parallels that of the human immunodeficiency virus (HIV) infection, which increases the risk of developing CC. Despite the progressive reduction of HIV prevalence in the past decade, the CC incidence and mortality rates in sub-Saharan Africa remain high. The heterogeneity of the distribution of the two diseases in the African continent, together with the different availability of human and material resources, stands in the way of finding an appropriate screening strategy. The lack of high-quality evidence on the prevention of CC for HIV-positive women, which is necessary for the implementation of efficient screening and treatment strategies, results in the absence of a clearly defined program, which is responsible for the low screening uptake and high mortality rates in sub-Saharan Africa. By taking advantage of the HIV-positive women’s frequent access to health facilities, one way to increase the CC screening coverage rates would be by providing integrated HIV and screening services within the same infrastructure. With the increasing availability of cost-effective methods, screening is becoming more and more available to women who have limited access to health care. Moreover, the introduction of point-of-care technologies for human papillomavirus testing and the subsequent implementation of screen-and-treat strategies, by reducing the number of clinical appointments and, in the long term, the loss to follow-up rates, open up new opportunities for all women, regardless of their HIV status. The purpose of this review is to provide an insight into the different screening practices for CC in order to help define one that is adapted to the resources and necessities of HIV-positive women living in middle-to-low income countries. Keywords: cervical cancer, screening, human papillomavirus (HPV), human immunodeficiency virus (HIV)